Ethical considerations of COVID-19 and compulsory vaccination: An Indian Viewpoint - R Harish; MG Rajkumar; K N Shashidhar (Journal of Clinical and Biomedical Sciences)
Following a devastating second wave of COVID-19, initiatives were taken to vaccinate India's eligible population, despite various barriers such as vaccine shortages, logistics, and popular skepticism of vaccination. India could manage to vaccinate 100 crore population.1 This has resulted in the manifestation of a seminal issue of autonomy vis a vis public health. The Central Government has evidently stated that vaccination is voluntary. However, there have been a few instances of coercive vaccination throughout India. This article debates the ethical contemplations and limitations of COVID-19 and compulsory vaccination across the Indian population